The Role of Parental Communication in Improving The Language Intelligence of 4-5 Year Old Children - Rahmat, Gina Khoeronnisa; Katoningsih, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The development of language intelligence in early childhood is a crucial foundation for their future communication skills. This research is important because many young children do not receive consistent language stimulation at home, while studies on the synergy of parent-teacher communication in the PAUD context-especially in local settings like BA Aisyiyah G-are still limited. This descriptive qualitative research was conducted over three months, from March to May 2025. Data sources included observations of communication practices, parent-teacher interviews, documentation, and school literature and documents. The research instruments consisted of observation guidelines, interview guides, and documentation formats. Data analysis followed the stages of reduction, presentation, and conclusion drawing according to Miles & Huberman. The results indicate that parental communication through consistent verbal stimulation at home plays a significant role in improving children's language intelligence. Teachers also reinforced this stimulation through storytelling and role-play activities, resulting in synergy between stimulation at home and at school resulting in improvements in children's ability to express ideas, enrich vocabulary, and construct sentences effectively. The findings emphasize the importance of simultaneous involvement between parents and teachers to optimize the language development of children aged 4-5 years.